1997
DOI: 10.1002/(sici)1097-0134(199701)27:1<110::aid-prot11>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Large differences are observed between the crystal and solution quaternary structures of allosteric aspartate transcarbamylase in the R state

Abstract: Solution scattering curves evaluated from the crystal structures of the T and R states of the allosteric enzyme aspartate transcarbamylase from Escherichia coli were compared with the experimental x-ray scattering patterns. Whereas the scattering from the crystal structure of the T state agrees with the experiment, large deviations reflecting a significant difference between the quaternary structures in the crystal and in solution are observed for the R state. The experimental curve of the R state was fitted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…8 More recently, small-angle X-ray scattering (SAXS) studies have shown that the change is even larger in solution, with an extra 3 Å expansion and ca 108 more rotations of the subunits as compared to the conformation in the crystal. 9,10 Mutation studies, combined with structural techniques, have provided significant insights on the role of individual amino acid residues and domain interactions. 8,11 Two main models, subsequently refined in a number of subtle variations, have been developed over the last several decades to account for the regulatory properties of allosteric enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recently, small-angle X-ray scattering (SAXS) studies have shown that the change is even larger in solution, with an extra 3 Å expansion and ca 108 more rotations of the subunits as compared to the conformation in the crystal. 9,10 Mutation studies, combined with structural techniques, have provided significant insights on the role of individual amino acid residues and domain interactions. 8,11 Two main models, subsequently refined in a number of subtle variations, have been developed over the last several decades to account for the regulatory properties of allosteric enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SAXS is able to provide information about the conformational changes of proteins in solution. The crystal environment can significantly differ from the physiological conditions in the cell, and the protein molecule conformation in solution can be different from its structure in the crystal [4]. Considerable differences between the crystal structure and the model of its structure proposed on the basis of the SAXS data in solution were observed for aspartate transcarbamylase from Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, the positions of the subsidiary maxima and minima observed in the experimental scattering of the PALA-bound ATCase could not be matched by the simulated scattering of the crystal structure, even with the addition of a hydration layer in the calculation. 138 It was thus proposed that PALA-bound ATCase is slightly more open in solution than depicted in the crystal structure and that crystal-packing forces not present in solution prevent the heterododecamer from adopting a more open conformation. Recent explicit solvent MD simulations of ATCase are consistent with an R-state that is more open than is seen in the PALA-bound crystal structure.…”
Section: Solution X-ray Scatteringmentioning
confidence: 99%